Uso de água residuária de suinocultura associada à adubação mineral no sistema de produção de grãos da Região Oeste do Paraná - Alves Neto, Alfredo José (2015)
Nutrients contained in swine wastewater (SW), are unbalanced and not fully available for the first crop, with the need for regionalized research, taking into account the characteristics of each site, such as rainfall, soil type and cropping systems of each region. With the objective of evaluating the influence of applications of ARS doses in soybean crop and second crop corn, chemical and physical properties of the soil, an experiment was conducted from september 2013 to august 2014, in the municipality of Cafelândia, western of Paraná, in the Copacol Center of Agricultural Research - CPA Copacol, in Dystroferric Red Latosol. In this experiment, was used five swine wastewater doses (0, 35, 70, 105 and 140 m3 ha-1 yr-1) and two sources of mineral fertilizer, absence and presence. The statistical design, was a randomized block with split plots, with four repetitions, allocated in the main plots factor doses, and in the subplots was allocated the mineral fertilizer factor, the soybean crop (summer 13/14) and maize second crop (winter 14/14). Biometric variables were evaluated, leaf levels of N, P, K, Cu and Zn in soybean and corn with their respective yields, with subsequent determination of economic analysis of SW doses. After second crop corn harvest, soil samples were collected in the layers 0 - 0,10 and 0,10 - 0,20 m to determine the C organic, P, K, Cu and Zn. Undisturbed soil core samples were collected in the layers 0 - 0,10, 0,10 - 0,20 and 0,20 - 0,30 m to determination of soil physical properties. With increasing of SW doses, a reduction in the biological nitrogen fixation in soybean, in contrast with increases in the weight of a thousand grains. In second crop corn, the SW doses increased productivity, thousand grain weight and grains moisture content. Identified an increase in the levels of P, K, Cu and Zn in the layer of 0 - 0,10 m, and increase in the P content in the layer of 0,10 - 0,20 m. The applications of SW doses kept the physical soil quality in layers sampled